A Highly Sensitive GFP Activation Assay for Detection of DNA Cleavage in Cells - Hu, Ziying; Zhang, Chengdong; Wang, Daqi; Gao, Siqi; Ong, Sang-Ging; Wang, Yongming; Zheng, Wei V. (Frontiers in Cell and Developmental Biology, 2021)
CRISPR/Cas9 nucleases hold great potential for gene therapy, but they frequently induce unwanted off-target cleavage. We previously developed a GFP activation assay for detection of DNA cleavage in cells. Here, we demonstrate two novel applications of this assay. First, we use this assay to confirm off-target cleavage that cannot be detected by targeted deep sequencing in cells before. Second, we use this approach to detect multiple alternative PAMs recognized by SpCas9. These noncanonical PAMs are associated with low cleavage activity, but targets associated with these PAMs must be considered as potential off-target sites. Taken together, the GFP activation assay is a powerful platform for DNA cleavage detection in cells.